Quo Vadis Desain Pengamanan Hakim dari Perbuatan Merendahkan Kehormatan dan Keluhuran Martabat Hakim (PMKH) di Indonesia - Ilmiyah, Zainatul (UI Scholars Hub, 2025)
Judges, as the main judicial actors in law enforcement, have an independent nature, both in terms of institutions and in terms of determining their decisions. However, in exercising their authority, judges are often faced with the risk of injury, both physical and psychological, by the public, who are not satisfied with the decisions made by the judges. With an empirical legal research method and using a conceptual approach, statute approach, and comparative approach, this study aims to find the best form in the design of an institutional model for judge and court security units. In this study, it was found that the judge and court security system has been normatively accommodated in several laws and regulations. However, in terms of implementation, there are still many obstacles, one of which is related to security human resources. So, an institutional design is needed for the security of judges and the courts. Several considerations in the formation of the institutional design of the judge's security unit are in terms of the constitutional importance of an institution and also the effectiveness of the institution. So, three institutional design models are offered. First, the idea of forming a new institution that has special authority in the security of judges and courts. The second institutional design is to cooperate between institutions in maintaining the security of judges and courts. The third design is to strengthen the authority of existing institutions. In addition, the security system of judges and the judiciary also requires guarantees, especially in terms of Human Resources, infrastructure, and budget.